1067 TELEMEDICINE FOR LIPID LEVELS FOLLOW UP AFTER ACUTE CORONARY SYNDROME. (15th December 2022) - Mautone, Francesco; Ragnatela, Ilaria; Di Nunno, Nicola; Corbo, Maria Delia; D´alessandro, Domenico Antonio; Ieva, Riccardo; Casavecchia, Grazia; Mele, Marco; Santoro, Francesco; Brunetti, Natale Daniele
Abstract: Background: The implementation of guidelines on LDL cholesterol levels after acute coronary syndrome (ACS) is very poor according to registries and surveys. Telemedicine could improve adherence to guidelines and facilitate clinical follow-up of patients with ACS, even with the limitations of Covid-19 pandemic. Aim of the study: To evaluate the efficacy of telemedicine follow-up in improving adherence to LDL guidelines and improving rates of prescription of PCSK9-inhibitors. Design and Methods: 650 consecutive patients discharged with diagnosis of ACS or Chronic CS were enrolled in the study and followed after 2 and 4 months. LDL levels and lipid lowering drug prescription were recorded. Data from 300 patients with ACS patients and <80 years were analyzed and LDL values of telemedicine followed-up patients (telephone/smartphone app/pc teleconsultation) were compared with controls. Results: Baseline mean LDL levels were 120 mg/dl, 55% of patients were naive of lipid lowering therapy. At second follow-up mean LDL levels were 55 mg/dl (p<0.05 vs baseline) and rates of prescription of statins, ezetimibe and PCSK9-inhibitors were 98%, 79%, and 18% respectively. Rates of subjects with LDL levels below recommended threshold were 4% at baseline, 39% at first follow-up, 53% at second follow-up (p<0.05). Patients followed up with telemedicine showed lower LDL levels at second follow-up (55vs72 mg/dl, p=0.08) and higher rates of subjects below recommended LDL levels (63%vs30%, p=0.05). Conclusions: Telemedicine follow-up may improve the implementation of guideline recommended LDL levels after ACS.